Combined Effects of 2-Methoxyestradiol (Hypoxia-Inducible Factor 1α Inhibitor) and Dasatinib (A Second-Generation Tyrosine Kinase Inhibitor) on Chronic Myelocytic Leukemia Cells - Yuexian Zhang; Heng Chen; Yunfeng Shen; Xin Zhou (Journal of Immunology Research)
Chronic myelocytic leukemia (CML) is a frequently encountered type of leukemia in China. Hypoxia-inducible factor 1 (HIF-1) serves as one of the most important factors of oxygen balance transcription. The activation of this gene mostly marks a poor outlook for cancer patients. To clarify the therapeutic effect of inhibiting this gene on CML, the present study is aimed at exploring the treatment effects of 2-methoxyestradiol (2-ME2), dasatinib alone, and combined both on K-562 cells and the possible mechanism of 2-ME2 in treating the disorder. The levels of HIF-1α, vascular endothelial growth factor (VEGF), and glutamate synthase 1 (GLU1) genes in K-562 cells were affected dose-dependently after 2-ME2 administration. 2-ME2 induced cell apoptosis by downregulating antiapoptotic protein expressions of Bcl-xl and Bcl-2. The therapeutic effect of single 2-ME2 was superior to single dasatinib, and the effect of combined therapy of both drugs produced better effectiveness than either of the single drug. Once the concentration of 2-ME2 exceeded 0.5 μM, downregulated C-myc gene expression could exert roles in anti-CML cell proliferation and inducing apoptosis. Dasatinib might participate in the inhibition of the C-myc pathway during this process whereas its effect remained not clear. Taken together, abnormal high expression of HIF-1α exerted an essential role in CML occurrence and development. Inhibition of this gene could markedly increase cell apoptosis in a dose-dependent fashion. Moreover, 2-ME2 could induce cell apoptosis by downregulating the C-myc gene and exert an apoptotic effect by downregulating Bcl-xl and Bcl-2 which act as antiapoptotic proteins.